Supervision Planning in Controlling activities in Educational Institutions - Rahmadi; Ayi Abdurahman; Ali Rohmad; Eny Haryaty (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
This journal aims to determine the planning of madrasa supervisors or supervision in an educational institution written in the Regulation of the Minister of Education and Culture no 143 of 2014. Various supervision activities control educational institutions. The researcher observes that educational institutions are successful and have excellent grades if a madrasa supervisor controls activities directly at school. On this basis, researchers are very interested in examining the supervision planning program and the control activities in educational institutions carried out by supervisors in conducting educational supervision management. This research is qualitative, namely, a research method that focuses on in-depth observation of phenomena regarding supervision in educational institutions to obtain a comprehensive study of a phenomenon—data collection techniques with interview and observation methods. The results found in this study are 1) Madrasah supervisor planning programs, including annual programs (long term), semester programs (medium term), Academic Supervision Plans (RPA), and Managerial Supervision Plans (RPM); 2) The way for the madrasa supervisor to be able to control correctly is to do it manually/ offline coaching and directing directly at the location of the institution and done online; 3) How the madrasa supervisor controls madrasah activities by visiting educational institutions, directly observing activities, using interviews or school component interviews, and using instruments or questionnaires distributed to all components.